Manajemen Sumberdaya Keluarga Peserta Program Pemberdayaan Masyarakat di Kabupaten Bogor - Tin Herawati; Basita Ginting Sugihen; Pang S Asngari; Djoko Susanto; Herien Puspitawati (Jurnal Penyuluhan, 2011)
Nowdays it is difficult for many families to achieve an ideal life, this situation cause, formulation managing human resource which has  a good quality is not optimal. The important thing must be carried out to make the families maintain their life is to manage the limited resource by the family resource management. This research analyzed the family resource management of participant in empowerment program and the factors that influenced them. The research design was crossectional study using survey method to collect data from 300 respondents. The result showed that highest percentage of respondent carried out the family resource management categorized as bad. There was a significant difference between the family resource management at Dramaga District and Leuwisadeng District or Pamijahan District (α<0.05). The factors which significantly influence the family resource management are income per capita, the family communication quality, the occupation status of spouse and the participation in extension program.Keywords:  family resource management, community empowerment, income per capita, extension program, communication quality